Hepatite B: uma DST ainda pouco lembrada - Tibúrcio, Alberto Saraiva; Passos, Mauro Romero Leal (Brazilian Journal of Sexually Transmitted Diseases, 1994)
Hepatitis B is a infectious disease with a high prevalence in the population. Among the differents transmission forms of the virus there is the sexual one,being that the sexual risk behavior increases the possibilities of this acqquisition. Further on the mise in evidence that hepatitis B is a S.T.D., are briefly discussed the etiopathogenesis, clinica! manifestations, prevention and treatment.